Empirical Support for the Tenets of Sport Participation and Physical Activity-Based Models: A Scoping Review - Gallant, François; Bélanger, Mathieu (Frontiers in Sports and Active Living, 2021)
Notwithstanding their wide-spread use, it is unclear what level of scientific evidence exists to support sport participation and physical activity-based models. Sport participation and physical activity-based models characterize different stages of sport involvement based on sport activities (organized and unorganized) individuals take part in throughout their lifespan. Objectives of this scoping review were to document and describe the nature of empirical support for tenets of sport participation and physical activity-based models describing the evolution of an individuals’ sport participation. Seventeen different sport participation models were identified through an iterative literature review, using a snowball search strategy and expert (n=8) consultation. Of the identified models, three described the evolution of an individual’s sport participation based on their participation in different activities at various stages of sport involvement and were retained for the review. A second literature review identified peer-reviewed publications supporting at least one tenet of these three models. Many tenets of retained models received some empirical support from some of the 38 publications identified, but some tenets were not tested. Most of the evidence supporting tenets originated from studies among elite-level athletes. Whereas some evidence exists to support current sport participation and physical activity models, more research is warranted, particularly among the general population of non-elite athletes, for the models to be used in full confidence to guide sport policies, programs and practices.